KELAYAKAN DAUN PANDAN WANGI SEBAGAI MASKER TRADISIONAL PERAWATAN KULIT KERING - Fadhilatur Rahmi; Prima Minerva (Jurnal Tata Rias dan Kecantikan, 2022)
Facial skin care generally has the objective of maintaining and improving skin health, as well as beautifying the skin's outer appearance. Pandan is a plant whose leaves are often used as an additional ingredient for food fragrance. Vitamin C found in fragrant pandan leaves has antioxidants that are better for facial skin. This study aims to a) analyze how to make a traditional pandan wangi leaf mask to moisturize dry facial skin, b) to analyze the quality of the pandan wangi leaf mask seen from the content of flavonoids, vitamin C, saponins found in fragrant pandan leaf masks, c) to analyze The quality of fragrant pandan leaf masks is seen from the texture, aroma, adhesion and preferences of researchers. This is a quasi experiment. The object of this research is  analyse fragrant pandan leaves which are made into natural mask powder. Tto analiyse  the flavonoids, vitamin C and saponins content, which is  carried out in the Chemical Laboratory of FMIPA UNP. And  to analyse  organoleptic test, by involving  7 panelists . Descriptive data  technique by displaying statistics and frequency. Based on the results of research, the process of making traditional pandan wangi leaf masks in this study was made in the form of powder, the quality of traditional pandan leaf masks based on laboratory test results showed that the content of flavonoids, vitamin C and saponins, based on organoleptic tests showed adhesion and preferences of panelists had a sufficient level high, while the texture aroma has the same value. Conclusion fragrant pandan leaves contain flavonoids, vitamin C and saponins. The organoleptic test showed the stickiness and preference of the panelists had a fairly high degree of initiation, while the aroma and texture had the same value.